54 Gbit/s OOK transmission using single‐mode VCSEL up to 2.2 km MMF. Issue 8 (1st April 2016) - Stepniak, G.; Lewandowski, A.; Kropp, J.R.; Ledentsov, N.N.; Shchukin, V.A.; Ledentsov, N.; Schaefer, G.; Agustin, M.; Turkiewicz, J.P.
Abstract : Successful 54 Gbit/s on–off keying (OOK) transmission over 2.2 km of multimode OM4 fibre is demonstrated. The decisive advantages of the single mode over multimode vertical cavity surface emitting laser (VCSEL) in transmission experiments are shown.